Classification of Guébie Within Kru - Sande, Hannah Leigh (My University, 2018)
Guébie, a Kru language spoken in Côte d’Ivoire, is currently doubly classified within Eastern Kru according to Ethnologue (Lewis et al. 2013). It is listed as a dialect of two distinct subgroups, Bété and Dida. This double classification is clearly problematic, and this paper provides the initial work towards addressing the correct classification of the language. Here I compare the phonological and syntactic properties of Guébie with surrounding Bété and Dida languages in order to determine its relatedness to each subgroup. I conclude that Guébie is more closely related to Vata, a Dida language, than to Bété.
Keywords: Guébie; Kru; Dida language